6
$\begingroup$

I want to prove that for $a,b,c>0$ we have

$$\sum_{cyc} \frac a{\sqrt{a^2+3b^2+3c^2}}= \frac a{\sqrt{a^2+3b^2+3c^2}}+\frac{b}{\sqrt{3a^2+b^2+3c^2}}+\frac{c}{\sqrt{3a^2+3b^2+c^2}}\le\frac3{\sqrt7}.$$

My first attempt: By Cauchy-Schwarz we have $$\left(\sum_{cyc} \frac a{\sqrt{a^2+3b^2+3c^2}}\right)^2\le3\sum_{cyc}\frac{a^2}{a^2+3b^2+3c^2}$$ so we only need to prove that the right-hand side is always less than $\frac{9}{7}$, but this is false. Failed

Second attempt: By Cauchy-Schwarz

$$\sum_{cyc} \frac a{\sqrt{a^2+3b^2+3c^2}}=\sum_{cyc} \frac 1{\sqrt{1+3\frac{b^2}{a^2}+3\frac{c^2}{a^2}}}\le\sum_{cyc} \frac{\sqrt 7}{1+3\frac{b}{a}+3\frac{c}a}$$

so it remains to prove that $$\sum_{cyc} \frac{a}{1+3b+3c}\le\frac37$$ but this is wrong for example for $a=1,b=1,c=2$. Failed

Third attempt: Let $S=3(a^2+b^2+c^2)$. We need to prove $$\sum_{cyc} \frac{a}{\sqrt{S-2a^2}}\le \frac37.$$ But $x\mapsto \frac{x}{\sqrt{S -2x^2}}$ is convex so Jensen has the wrong direction...

$\endgroup$
3
$\begingroup$

Just an observation, the equality is achieved not only for $a=b=c$, but also for $$(a^2 \colon b^2 \colon c^2) = (8\colon 1\colon 1)$$

$\bf{Added:}$

Define $$x=\frac{a^2}{a^2 + 3 b^2 + 3 c^2},\ y=\frac{b^2}{b^2 + 3 a^2 + 3 c^2},\ z=\frac{c^2}{c^2 + 3 a^2 + 3 b^2}$$

One checks (say by direct calculation) that $$28 x y z + 8(x y + x z + y z )+ x+y+z-1=0$$

So it is enough to show that the maximum of the function $\sqrt{x}+\sqrt{y}+\sqrt{z}$ on the part of the above surface in the first octant is $\frac{3}{\sqrt{7}}$. The Lagrange multiplier system $$28 x y z + 8(x y + x z + y z )+ x+y+z-1=0\\ t - x( 28 y z + 8 (y+z) + 1)^2 =0\\ t - y( 28 x z + 8 (x+z) + 1)^2 =0\\ t - z( 28 x y + 8 (x+y) + 1)^2 =0$$

is in fact not that hard to solve, if we use Groebner bases. First, by elimination we get the equation in $t$:

$$72313663744 t^7 - 207058475232 t^6 - 212349914280 t^5 + 806857109604 t^4 + 125825565483 t^3 - 784526490225 t^2=0$$ which factor nicely as $$t^2 (1372 t - 2025) (343 t - 729) (56 t + 81) (2744 t^2 - 1944 t - 6561)=0$$

Now one considers each of the possible positive values of $t$ and solves the system in $x$, $y$, $z$.

Case 1. $343 t - 729=0$. We get $x=y=z=\frac{1}{7}$

Case 2. $1372 t - 2025=0$. We get the solution $x=\frac{4}{7}$, $y=z=\frac{1}{28}$ and the cyclic permutation of it.

Case 3. $t = \frac{81(6 + 19\sqrt{2})}{1372}$

We get $x=\frac{-2 + 3 \sqrt{2}}{7}$, $y=z = \frac{-2 + 3 \sqrt{2}}{28}$ and the circular permutations.

Case 4. $t=0$ gives negative solutions, so we discard it

The inequality now follows, in the cases 1, 2, the functions takes the maximum value $\frac{3}{\sqrt{7}}$, in case 3 the value is smaller.

$\endgroup$
2
$\begingroup$

We need to prove that: $$\sum_{cyc}\sqrt{\frac{a}{a+3b+3c}}\leq\frac{3}{\sqrt7},$$ where $a$, $b$ and $c$ are positive numbers.

Indeed, by C-S $$\left(\sum_{cyc}\sqrt{\frac{a}{a+3b+3c}}\right)^2\leq\sum_{cyc}\frac{a}{(a+3b+3c)(17a+2b+2c)}\sum_{cyc}(17a+2b+2c).$$ Thus, it's enough to prove that: $$\sum_{cyc}\frac{a}{(a+3b+3c)(17a+2b+2c)}\leq\frac{3}{49(a+b+c)}.$$ Now, let $a+b+c=3u$, $ab+ac+bc=3v^2$ and $abc=w^3$.

Thus, we need to prove that: $$\sum_{cyc}\frac{a}{(9u-2a)(6u+15a)}\leq\frac{1}{49u}$$ or $$49u\sum_{cyc}a(9u-2b)(9u-2c)(2u+5b)(2u+5c)\leq3\prod_{cyc}((9u-2a)(2u+5a)).$$ We'll prove that the last inequality is true even for any reals $a$, $b$ and $c$.

Indeed, since $\sum\limits_{cyc}a(9u-2b)(9u-2c)(2u+5b)(2u+5c)$ is a fifth degree polynomial,

the last inequality is equivalent to $f(w^3)\geq0,$ where $$f(w^3)=-3000w^6+A(u,v^2)w^3+B(u,v^2).$$ But $f$ is a concave function.

Thus, $f$ gets a minimal value for an extreme value of $w^3$, which happens for equality case of two variables.

Since the last inequality is an even degree, homogeneous and symmetrical, it's enough to assume $b=c=1,$ which gives $$\frac{a}{(a+6)(17a+4)}+\frac{2}{(3a+4)(2a+19)}\leq\frac{3}{49(a+2)}$$ or $$(a-1)^2(a-8)^2\geq0$$ and we are done!

$\endgroup$
  • 1
    $\begingroup$ Can I ask: when you use Cauchy-Schwarz, do you look for $x,y,z$ such that: $$\frac{7a}{(a+3b+3c)(xa+yb+zc)^2}=\frac{7b}{(b+3a+3c)(xb+ya+zc)^2}=\frac{7c}{(c+3a+3b)(xc+ya+zb)^2}$$ for both equality cases? $\endgroup$ – LHF Feb 23 at 15:28
  • 2
    $\begingroup$ @Atticus Yes, of course. Because our vectors should be parallel. $\endgroup$ – Michael Rozenberg Feb 23 at 15:33
2
$\begingroup$

Alternative proof:

Use the argument in https://artofproblemsolving.com/community/c6h1822770p12198977 or https://artofproblemsolving.com/community/c6h548438p3180154.

Let $x, y, z > 0$ such that $\frac{7a^2}{a^2 + 3b^2 + 3c^2} = x^2, \ \frac{7b^2}{b^2 + 3c^2 + 3a^2} = y^2, \ \frac{7c^2}{c^2 + 3a^2 + 3b^2} = z^2$. It is not hard to obtain $$F(x, y, z) = 4 x^2 y^2 z^2+8 x^2 y^2+8 x^2 z^2+8 y^2 z^2+7 x^2+7 y^2+7 z^2-49 = 0.$$

It suffices to prove that if $x, y, z > 0$ and $F(x,y,z) = 0$, then $x+y+z \le 3$. It suffices to prove that if $x, y, z > 0$ and $x + y + z > 3$, then $F(x, y, z) > 0$. Note that $F(\alpha x, \alpha y, \alpha z) > F(x, y, z)$ for any $\alpha > 1$ and $x, y, z > 0$. Thus, it suffices to prove that if $x, y, z > 0$ and $x+y+z = 3$, then $F(x, y, z) \ge 0$.

We use pqr method. Let $p = x + y + z = 3$, $q = xy + yz + zx$ and $r = xyz$. From $p^2 \ge 3q$, we have $q \le 3$. Let $q = 3(1-u^2)$ for $0 \le u\le 1$. We have \begin{align} (x-y)^2(y-z)^2(z-x)^2 &= -4p^3r+p^2q^2+18pqr-4q^3-27r^2\\ & = 108u^6 - 27(3u^2+r-1)^2 \end{align} which results in $108u^6 - 27(3u^2+r-1)^2 \ge 0$ and hence $r \le (2u+1)(1-u)^2 \le 3$. Thus, we have \begin{align} F(x, y, z) &= 7p^2-16pr+8q^2+4r^2-14q-49 \\ &= 4(6-r)^2+72u^4-102u^2-100\\ &\ge 4(6 - (2u+1)(1-u)^2)^2 + 72u^4-102u^2-100\\ &= 2u^2(2u^2-4u+9)(2u-1)^2\\ &\ge 0. \end{align} We are done.

$\endgroup$
1
$\begingroup$

We need to prove that:

$$\sqrt{\frac{a}{a+3b+3c}}+\sqrt{\frac{b}{b+3c+3a}}+\sqrt{\frac{c}{c+3a+3b}}\leq\frac{3}{\sqrt7}$$

Let's normalize with $a+b+c=3$. Then the inequality is equivalent with:

$$\sqrt{\frac{a}{9-2a}}+\sqrt{\frac{b}{9-2b}}+\sqrt{\frac{c}{9-2c}}\leq \frac{3}{\sqrt{2}}$$

Without loss of generality suppose that $a\le b\le c$. Then we have $a+b\leq 2$ and we will prove:

$$\sqrt{\frac{a}{9-2a}}+\sqrt{\frac{b}{9-2b}} \leq \sqrt{\frac{2(a+b)}{9-a-b}}$$

Squaring twice, this is equivalent with:

$$\frac{(a-b)^2[729+81(a+b)^2-486(a+b)-16ab(a+b)]}{(9-2a)^2(9-2b)^2(9-a-b)^2}\geq 0$$

We have $16ab(a+b)\leq 16(a+b)$ and

$$729+81x^2-502x\geq 0, \text{ when }x \leq 2$$

It remains to prove that:

$$\sqrt{\frac{14(3-c)}{6+c}}+\sqrt{\frac{7c}{9-2c}}\leq 3$$

Squaring twice this is equivalent with:

$$\frac{81(c-1)^2 (12 - 5 c)^2}{(9 - 2 c)^2 (6 + c)^2}\geq 0$$

which gives the two equality cases.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.